2015
DOI: 10.1016/j.biopsych.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide Association Study of Autism Using the Simons Simplex Collection: Does Reducing Phenotypic Heterogeneity in Autism Increase Genetic Homogeneity?

Abstract: Background Phenotypic heterogeneity in autism has long been conjectured to be a major hindrance to the discovery of genetic risk factors, leading to numerous attempts to stratify children based on phenotype to increase power of discovery studies. This approach, however, is based on the hypothesis that phenotypic heterogeneity closely maps to genetic variation, which has not been tested. Our study examines the impact of sub-phenotyping of a well-characterized ASD sample on genetic homogeneity and the ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 74 publications
1
113
1
1
Order By: Relevance
“…Similarly, Chaste et al (2015) found that subgrouping ASD by distinct phenotypes did not result in finding sets of genetic variants that were unique to distinct clinical phenotypes. In fact, fewer and greater numbers of overlapping genetic variants were reported across the ASD phenotypic groups.…”
Section: Rates Of Recovery From Asd Are Variedmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Chaste et al (2015) found that subgrouping ASD by distinct phenotypes did not result in finding sets of genetic variants that were unique to distinct clinical phenotypes. In fact, fewer and greater numbers of overlapping genetic variants were reported across the ASD phenotypic groups.…”
Section: Rates Of Recovery From Asd Are Variedmentioning
confidence: 99%
“…In fact, fewer and greater numbers of overlapping genetic variants were reported across the ASD phenotypic groups. Chaste et al (2015) nonetheless argued that clinical phenotypes must have some Bpower for discovering genetic associations^(p. 781).…”
Section: Rates Of Recovery From Asd Are Variedmentioning
confidence: 99%
See 1 more Smart Citation
“…This data was used in a reconstruction of functional networks linking the antibodies targets to genes relevant to autism (Supplementary table 2). The genes were chosen via GWAS studies by the correlation of relevant SNPs to autistic phenotype (genes) [28][29][30][31].…”
Section: Data Miningmentioning
confidence: 99%
“…However, such an approach is risky for common, non-Mendelian psychiatric disorders given: 1) current lack of insight into relevant subtypes; and 2) reduced sample size. A GWAS based on ~2,500 cases in the Simons Simplex Collection ASD cohort showed no improvement in the proportion of genetic heritability explained by the top SNPs accounting for changes in sample size for over 10 phenotypic characteristics 49 . In contrast, a GWAS of a nonpsychiatric phenotype, bone mineral density, showed benefits of subgrouping, leading to the identification of 16 new loci 50 .…”
Section: Strategies To Improve Locus Discovery In Wgsmentioning
confidence: 99%